2012
DOI: 10.1029/2012jd017921
|View full text |Cite
|
Sign up to set email alerts
|

Birth of ball lightning

Abstract: [1] Many observations of ball lightning report a ball of light, about 10 cm in diameter, moving at about walking speed, lasting up to 20 s and frequently existing inside of houses and even aeroplanes. The present paper reports detailed observations of the initiation or birth of ball lightning. In two cases, navigation crew of aircraft saw ball lightning form at the windscreen inside the cockpit of their planes. In the first case, the ball lightning occurred during a thunderstorm, with much lightning activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
(26 reference statements)
0
21
0
Order By: Relevance
“…The color of bright bluish white or orange white can be seen during the lifetime of 2-5 s. Immediately, Stephan and Massey [9] carried out the similar experiment, producing silicon-based luminous balls with diameters of 0.1-1 mm. The estimated temperature of these balls is about 3140 K. For external-energy theory, Lowke et al proposed that BL is regarded as a pulsed electric discharge with frequency on a microsecond time scale, which can provide an explanation for the formation, lifetime, energy source, and motion of natural BL [10,11]. The most well-known model was proposed by Kapitza [12], hypothesizing that an intense radio frequency electromagnetic field could supply the necessary energy to form and sustain BL.…”
mentioning
confidence: 99%
“…The color of bright bluish white or orange white can be seen during the lifetime of 2-5 s. Immediately, Stephan and Massey [9] carried out the similar experiment, producing silicon-based luminous balls with diameters of 0.1-1 mm. The estimated temperature of these balls is about 3140 K. For external-energy theory, Lowke et al proposed that BL is regarded as a pulsed electric discharge with frequency on a microsecond time scale, which can provide an explanation for the formation, lifetime, energy source, and motion of natural BL [10,11]. The most well-known model was proposed by Kapitza [12], hypothesizing that an intense radio frequency electromagnetic field could supply the necessary energy to form and sustain BL.…”
mentioning
confidence: 99%
“…This episode has been interpreted by Bicknell (1975) as a ball‐lightning, which is an atmospheric electrical phenomenon usually associated with thunderstorms (Carbognani 2016). Conversely, the description given by Obsequens seems to be not consistent with a ball‐lightning because the latter is usually described as a glowing ball 10–20 cm in diameter moving at about walking speed (Lowke et al 2012). Therefore, we ascribed this fall to a superbolide brighter than the Sun similar to that occurred in Chelyabinsk in 2013 (Hartmann 2015; Gorkavyi et al 2019) and in any case reaching a magnitude of at least −20.…”
Section: Resultsmentioning
confidence: 99%
“…The stability and dynamics of ball lightning are of interest for plasma studies. Four of the five authors found on this theme (Bychkov et al, 2010;Hughes, 2011;Lowke et al, 2012;Lozneanu et al, 2006) describe the mechanics of ball lightning. Abrahamson & Dinniss (2000) also write about the changes to soil in addition during a ball lightning strike.…”
Section: Some Ball Lightning Featuresmentioning
confidence: 99%